2015
DOI: 10.3329/sja.v13i1.24184
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability, correlation and path analysis for yield and yield components in promising rice (Oryza sativa L.) genotypes

Abstract: Seventy three rice varieties were evaluated for their variability with regards to yield and yield components. Estimates of heritability and genetic advance in per cent of mean were also obtained for the above traits. In addition, studies on character associations and path coefficients were also undertaken. The results revealed high variability, heritability and genetic advance in per cent of mean for grain yield while panicle bearing tillers and 1000 grain weight had recorded high heritability coupled with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 5 publications
25
15
0
Order By: Relevance
“…Plant height showed positive and significant correlation with culm length (r p =0.995**), flag leaf length (r p =0.687**), panicle length (r p =0.403*), above ground biomass yield (r p =0.337*) and thousand grains weight (r p =0.464**) and negative and significant correlation with harvest index (r p =-0.566**). The finding is in conformity with Ghosal et al (2010) and Kishore et al (2015) for panicle length. Moreover, panicle length showed significant and positive association with culm length (r p =0.333*), flag leaf length (r p =0.539**), filled grains per panicle (r p =0.426**), total grains per panicle (r p =0.387*) and biomass yield (r p =0.539**) but non-significant association with unfilled grain per panicle (rp=0.218), fertile tillers per plant (r p =0.106), thousand grains weight (r p =0.084) and harvest index (r p =-0.281).…”
Section: Phenotypic Correlation Between the Traitssupporting
confidence: 86%
See 1 more Smart Citation
“…Plant height showed positive and significant correlation with culm length (r p =0.995**), flag leaf length (r p =0.687**), panicle length (r p =0.403*), above ground biomass yield (r p =0.337*) and thousand grains weight (r p =0.464**) and negative and significant correlation with harvest index (r p =-0.566**). The finding is in conformity with Ghosal et al (2010) and Kishore et al (2015) for panicle length. Moreover, panicle length showed significant and positive association with culm length (r p =0.333*), flag leaf length (r p =0.539**), filled grains per panicle (r p =0.426**), total grains per panicle (r p =0.387*) and biomass yield (r p =0.539**) but non-significant association with unfilled grain per panicle (rp=0.218), fertile tillers per plant (r p =0.106), thousand grains weight (r p =0.084) and harvest index (r p =-0.281).…”
Section: Phenotypic Correlation Between the Traitssupporting
confidence: 86%
“…Likewise, Iftekharuddaula et al (2001) reported highily significant and positive correlation of plant height with panicle length and negative correlation for harvest index. Similarly, Ghosal et al (2010), Babu et al (2012) and Kishore et al (2015) reported positive correlation of plant height with panicle length. Panicle length was positively and significantly associated with culm length (r g =0.369*), flag leaf length (r g =0.511**), filled grain per panicle (r g =0.503**), thousand grains weight (r g =0.405*), unfilled grain per panicle (r g =0.500**), total grain per panicle (r g =0.524**) and biomass yield (r g =0.729**).…”
Section: Genotypic Correlation Coefficientmentioning
confidence: 75%
“…Furthermore, in contrast to our results, they reported a significant positive correlation between PL and GP. Similar to the results of current work, a significant positive correlation between PH and PL was found by Hossain et al, (2015) and Kishore et al, (2015) while, Rai et al, (2015) reported it significant, but negative. According to our observations and in agreement with Hossain et al, (2015), the correlation between GW and GP was significant and positive while, Kishore et al, (2015) reported it significantly negative.…”
Section: Conventional and Sequential Path Analysissupporting
confidence: 81%
“…Similar to the results of current work, a significant positive correlation between PH and PL was found by Hossain et al, (2015) and Kishore et al, (2015) while, Rai et al, (2015) reported it significant, but negative. According to our observations and in agreement with Hossain et al, (2015), the correlation between GW and GP was significant and positive while, Kishore et al, (2015) reported it significantly negative. A significant positive correlation between GW and GL was reported by Haider et al, (2014) and Kumar (2015) while, like current study, Rafii et al, (2014) found no such correlation.…”
Section: Conventional and Sequential Path Analysissupporting
confidence: 81%
“…A critical analysis of the genetic variability parameters, namely, genotypic variance coefficient (GVC), phenotypic of variance coefficient (PVC), heritability and genetic progress for various economically important traits is a major precondition for any breeders working in crop improvement programs [35]. The values of GVC, PVC and heritability (H 2 %) taken alone give no indication of the importance of the genetic progress that would result from the selection of the best individuals, but coupled with the genetic gain compared to the average EGG, this value is more useful [31].…”
Section: Discussionmentioning
confidence: 99%